1997
DOI: 10.1143/jjap.36.6818
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dielectric Properties of (Ca1-xNd2x/3)TiO3

Abstract: (Ca1- x Nd2 x /3)TiO3 sintered samples are fabricated with 0≦x≦1 and the crystal structure and dielectric properties are investigated. It is shown that (Ca1- x Nd2 x /3)TiO3 has an orthorhombic GdFeO3-type structure for 0≦x≦0.69 and an La2/3TiO3-type double-layered perovskite struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 9 publications
5
60
0
Order By: Relevance
“…2),5)8), 12) The EDS data in Table 1 confirmed this mechanism derivation. Because of the growing Q©f value in 0¯x¯0.1 with declined grain size, for the declination of the Q©f value of 0.15¯x¯0.2, high tangent loss secondary phase probably played a key role.…”
Section: )supporting
confidence: 68%
“…2),5)8), 12) The EDS data in Table 1 confirmed this mechanism derivation. Because of the growing Q©f value in 0¯x¯0.1 with declined grain size, for the declination of the Q©f value of 0.15¯x¯0.2, high tangent loss secondary phase probably played a key role.…”
Section: )supporting
confidence: 68%
“…The difference of ionic radius and electronegativity between the Mg 2+ and Nb 5+ in B-site originates the 1:2 ordering structure in Ca(Mg 1/3 Nb 2/3 )O 3 [12]. On the other hand, Masashi et al have suggested that Ca 1−x Nd 2x/3 TiO 3 (x≦0.69) could be refined as orthorhombic structure with space group Pnma(62) [9]. peaks are displaced to higher 2θ angles with increasing Ca 0.61 Nd 0.26 TiO 3 content.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on such solid solution systems have been reported [3][4][5][6][7], where the microwave dielectric characteristics were discussed together with crystal structures and phase transitions. On the other hand, the A-site deficient perovskites Ca 1−x Ln 2x/3 TiO 3 (Ln = La, Nd and Sm) have much higher Q value and smaller t f than those of CaTiO 3 [8][9][10]. Therefore, one can expect to obtain the temperature stable microwave dielectric ceramics combined with a higher dielectric constant and a higher Q value in the systems of Ca(B,B″)O 3 -Ca 1−x Ln 2x/3 TiO 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase variation was similar to Casubstituted Ba6-3xSm8+2xTi18O54 ceramics. 9) Because the diffraction peaks of perovskites phase might overlap with those of the tungsten bronze type phase, the perovskites phase was identified from the change of relative intensitis of diffraction peaks until the x was beyond 0.8.…”
Section: +mentioning
confidence: 99%